2002
DOI: 10.1002/ima.10009
|View full text |Cite
|
Sign up to set email alerts
|

A neural network‐based nonlinear filter for image enhancement

Abstract: This paper explores a novel neural network-based nonlinear filter that has the ability to remove mixed noises and sharpen the edges in noise-corrupted digital images. The noise is assumed to be a mixture of both Gaussian and impulse types. Initially, a nonlinear filter is used to reduce the noise. The smoothed image is then combined with the output of an edge detector using a synthesizer to provide the effect of noise reducing and edge sharpening. The smoother and synthesizer are designed by using layered neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…With the rapid development of the image processing and digit recognition, lots of progress is made in the field [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Zhang et al explored a novel neural network-based nonlinear filter, which was able to remove mixed noises and sharpen the edges in noisecorrupted digital images [1]. Simulation results showed that the proposed filter was able to effectively remove the mixed Gaussian and impulsive noises and sharpen the edges.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of the image processing and digit recognition, lots of progress is made in the field [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Zhang et al explored a novel neural network-based nonlinear filter, which was able to remove mixed noises and sharpen the edges in noisecorrupted digital images [1]. Simulation results showed that the proposed filter was able to effectively remove the mixed Gaussian and impulsive noises and sharpen the edges.…”
Section: Introductionmentioning
confidence: 99%